KEPEMIMPINAN KHARISMATIK KYAI DAN MOTIVASI KERJA PENGARUHNYA TERHADAP KINERJA GURU (Pondok Pesantren Ppai Darun Najah, Ngijo, Karangploso, Malang) - Taufiki Fakkarudin Assilahi; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTION The purpose of this study is to describe charismatic leadership kyai, work motivation and performance of teachers and to know the influence charismatic kyai, work motivation on teacher performance partially or simultaneously. This research method using quantitative method. This type of research is explanatoryThe sample of this research is boarding school teacher PPAI Darun Najah by using saturated sampling, that is as much as 62 respondents. Methods of data collection using questionnaires. the analytical method used I n this research is multiple regression analysis with SPSS 20.0 for windows.The results of this study indicate that: (1) there is a positive and significant influence of kyai charismatic leadership on teacher performance (2) there is a positive influence and signifies work motivation on teacher performance. Keywords:  Kyai Charismatic Leadership, Work Motivation and Teacher  Performance